Evaluasi Mutu Fisikokimia Roti Berserat Tinggi Berbahan Baku Kulit Biji Kedelai dan Bekatul - H. Wahyudi, Richardus Widodo (AGROKNOW, 2013)
Abstract. Along with increased knowledge and awareness of the health of the food consumed, people now consume safe food is very important. Food products not only work satiate and satisfy any taste but also be safe and healthy. One food trend that is increasingly looking more and more prominent functional food products. Among many functional foods, the more prominent is food that can lower high cholesterol in the blood, ie by increasing consumption of soluble fiber that can not be digested. One source of food fiber product which is popular in the community began to bread wheat, which is bread made from grain (whole wheat bread). Unfortunately, wheat seeds in Indonesia are mostly imported products. It required local products that can replace the function of wheat seeds in the manufacture of fiber-rich bread. Two potential sources of food fiber are removed the seed coat of soybean and rice bran.Â Research conducted using Completely Randomized Design (CRD) which is repeated as many as 3 (three) times. As the primary treatment is weight ratio of flour and a mixed source of fiber, with the substitution level fiber sources (soy skin or rice bran) at 5%, 10% and 15% and plus one control treatment (C) 100% wheat flour. The parameters tested were: the physical properties of bread (the texture and specific volume), the chemical (proximate test and crude fiber content), and hedonic sensory test Scoring Scale (color, flavor, taste, tenderness, uniformity of pores). The results showed that the substitution of soybean seed coat or bran may affect the quality of bread produced by either physical (volume type and texture), chemical (water content) and organoleptic (flavor and taste). Volume tends to decrease the type of bread, harder texture and distinctive flavor and taste of soy and rice bran that tend to not like by panelists.Kata kunci : roti tawar, kulit biji kedelai, bekatul, pangan fungsional